Personalized support of parents of extremely preterm infants before, during and after birth. Issue 3 (June 2022) - Haward, Marlyse F.; Luu, Thuy Mai; Pearce, Rebecca; Janvier, Annie
Abstract: The emotional turmoil associated with extremely preterm birth is inescapable parents. How each parent handles the unexpected, makes sense of the unknown and learns to parent their child is uniquely personal. A rigid standardized approach to support families through their journey before and during neonatal intensive care disregards this individuality. This article reviews general concepts and practices that can be learned and applied by clinicians to promote resiliency and help parents cope adaptively. This review will describe how to personalize parenting support during the antenatal consultation and hospitalization for parents of extremely premature infants. To facilitate this, mindsets and care delivery models need to shift from inflexible standardized protocols to flexible guidelines that enable personalized communications, support structures and care delivery models tailored to each person's characteristics, preferences, and values.